Investigation of ?-Amylase Production with Bacillus amyloliquefaciens in a Cocurrent Downflow Contacting Reactor - Orhan, Ramazan; Dursun, Gulbeyi (Walter de Gruyter Gmbh, 2016)
The cocurrent downflow contacting reactor (CDCR) has a high oxygen transfer rate by providing the effective the gas-liquid contact. This property is an advantage for enzyme production. In this study, the CDCR was used for the production of alpha-amylase by Bacillus amyloliquefaciens for different starch concentrations in the range of 7.5-17.5 g l(-1) at constant air and liquid flow rates. The values of the volumetric oxygen transfer coefficient (k(L)alpha) and specific oxygen uptake rate (q(O2)) were determined during enzyme production. It has been found that the starch concentration has great effect on the enzyme activity. Maximum enzyme activity (1,000 IU ml(-1)) was obtained in the fermentation broth containing of 15 g l-1 starch concentration at 37 degrees C and pH 7 for 28 h. The k(L)alpha and q(O2) values were determined to be 175.83 h(-1) and 47.5 mg O-2 g(-1)cell h(-1), respectively.
Keywords: CDCR; Bacillus amyloliquefaciens; alpha-amylase; volumetric oxygen mass transfer coefficient